SEBARAN JENIS TENGKAWANG (Shorea Spp) di HUTAN TEMBAWANG DESA LABIAN KECAMATAN BATANG LUPAR KAPUAS HULU KALIMANTAN BARAT - Rikando, Riki; Latifah, Siti; Manurung, Togar Fernando (JURNAL HUTAN LESTARI, 2019)
Kapuas Hulu Regency is lowland area of tropical rain forest which has many Dipterocarpaceae, one of  which is tengkawang ( Shorea spp). Forests in Kapuas Hulu are currently under threat because of the widespread exploitation of land  on a large scale without considering the balance of the ecosystem. Tembawang forest in Labian village has the potential of tengkawang trees which have not been known  to be distributed based on topography where is grows. The aim of this study is to obtian the distribution of tengkawang (Shorea spp) species based on topography in the tembawang forest in the Labian district of Kapuas hulu, Kalimantan. This research was conducted using a survey method with samples taken in census in six tembawang. The research results show that there are 4 species of tengkawang (Shorea spp). The disribution of tengkawang spesies based on the from of thopography of Shorea marcophylla Aston and Shorea seminis Slooten grew on the topografhy of the valley with a height of 0 - 87 meter above sea level and slope of 9% - 23 % in all tembawang spread in group closed to waterside and scattered clustered at the Shorea  pinanga Scheff  and Shorea stenoptera Bruck spread on slope in groups with a height of 60-70 meter above sea level. Keywords : distributions, dipterocarpaceae, tembawang, tengkawang